Gentamicin Variably Affects amrZ and rhl gene Expression in Swarmer Cells of Pseudomonas aeruginosa - Fadhil, Khaldoon Hasan; Al-Mathkhury, Harith Jabbar Fahad (Iraqi Journal of Science, 2022)
Swarming is one of the most important virulence factors used by bacteria to invade new sites. This study aimed to test the effects of gentamicin on swarming motility of Pseudomonas aeruginosa, both phenotypically and molecularly. The present results revealed that 11/25 isolates had gentamicin MIC of 1024 µg/ml. However, gentamicin at sub-minimal inhibitory concentration significantly (P< 0.05) reduced the diameter of swarming in all P. aeruginosa isolates. Noticeably the mean and median swarming diameter before treatment with gentamicin 5.557 and 5.816 cm respectively had significantly (P < 0.001) reduced to 0.871 and 0.766 cm respectively. At the molecular level, amrZ (a global regulator of multiple genes) and rhl (responsible for rhamnolipid production) were variably affected by gentamicin. More likely it can be concluded that amrZ and rhl are not fully responsible for swarming in P. aeruginosa isolates.